(untitled) (Proceedings of the International Conference on Social Sciences, 2018)
Oppression is, by far, not a new phenomenon. Since times immemorial there have been stories of oppression, told and retold. The oppressed tell the stories from their perspective, where they are the downtrodden and exploited. The oppressors, on the other hand, glorify their actions as powerful and the way the oppressed were meant to serve them. No matter what the perspective, no matter what the time, one sector showing its power over another has been a common occurrence. This paper is an attempt to outline this never changing and everlasting occurrence of oppression. The paper covers a present day incident of oppression on a scheduled tribe in the state of Jharkhand, India, called the Birhor Tribe. The paper looks at the conditions of the tribal people, their oppression by authorities and people in power and their day to day struggle. The paper finally tries to explain the current form in which oppression occurs with the help of established psychological theories.